(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study digs into the varied terrain of digital transformation in India’s higher education industry. Higher education institutions around the country are embracing digital technologies to transform teaching, learning, administration, and student services. The study uses a mixed-methods approach and includes 500 directors, teachers, and educators from various institutions across India. The study looks into the extent to which digital technology has been integrated, the influence of obstacles and opportunities, and the overall quality and efficiency of higher education in the digital age. The results of regression analysis confirm considerable disparities in digital technology integration and highlight the important influence of challenges and possibilities on educational quality and efficiency. Key findings highlight the need for tailored strategies and investments to bridge disparities and foster equitable digital transformation. The study contributes to the scholarly discourse on higher education transformation and offers actionable insights for policymakers, institutional leaders, and educators.